Should more patients be offered repair for mitral valve endocarditis? a single-centre 15-year experience - Clarissa Ng Yin Ling; David Bleetman; Soumik Pal; Hing Chi Kristie Leung; Habib Khan; Donald Whitaker; Olaf Wendler; Ranjit Deshpande; Max Baghai (figshare, 2022)
Abstract Objective To describe the long-term outcomes of mitral valve repair (MVr) versus mitral valve replacement (MVR) in patients with native valve infective endocarditis (IE) at a centre with high-repair rates. Methods We conducted a retrospective single-centre cohort study. From 2005 to 2021, 183 patients with active or healed native valve IE were included. The primary outcome was long-term mortality. Patient status was last confirmed 31 March 2021. Secondary outcomes were post-operative MR, MV reoperation, length of post-operative intensive care stay and total hospital stay. Results 85 patients (46.4%) underwent MVr and 98 (53.6%) underwent MVR. Follow-up was 98.9% complete. Mean follow-up time was 5.3 years with 17% of patients reaching a follow-up time of over 10 years. There were 47 deaths (25.7%) within the follow-up period. MVR patients were more likely to have higher logistic EuroSCORE, active IE and were less likely to have elective surgery. In multivariate Cox proportional hazards analysis, there was no significant difference in long-term mortality between MVr and MVR groups (hazard ratio 1.09, 95% confidence interval [0.59–2.00]). In Kaplan–Meier analysis, MVR patients had a higher all-cause mortality although there was no significant difference at the endpoint. Propensity score matching analysis showed a significantly higher mortality in the replacement group instead (p = 0.002), Subgroup analysis revealed there remained no significant difference in mortality even in patients with active IE (P-interaction = 0.859) or non-elective surgery (P-interaction = 0.122). MV reoperation (odds ratio 1.00 [0.24–4.12]), post-operative intensive care stay (p = 0.9650) and total hospital stay (p = 0.9144) were comparable. Conclusions Our data demonstrates repair was at least non-inferior to replacement in IE, supporting more aggressive use of repair. There is no reason the general principle of why repair is superior to replacement should not hold in IE, with enough operator expertise. Other experienced units should be encouraged to increase repair rates as feasible in line with current guidelines.
Keywords: Medicine; 69999 Biological Sciences not elsewhere classified; Science Policy; 111714 Mental Health